Increasing faculty’s competence in digital accessibility for inclusive education: a systematic literature review - Bong, Way Kiat; Chen, Weiqin (International Journal of Inclusive Education, 2021)
The use of information and communications technology (ICT) in higher education institutions has increased in the past 20 years. While ICT has brought many benefits to students and faculty, research shows that it also creates barriers and challenges for students with disabilities due to the inaccessibility of digital tools and learning materials. Faculty members play an important role in inclusive higher education. Previous studies have emphasised the need to train faculty about digital accessibility to achieve inclusion in higher education. This systematic literature review aims to study existing work on increasing the faculty members’ competence in providing accessible and inclusive digital learning materials and environments to students in higher education. Sixteen peer-reviewed papers were included and analysed. Most trainings included topics on disability and awareness, legislation, and methods of producing accessible digital materials and providing inclusive digital learning environments. While surveys and interviews were mostly used to evaluate training outcomes, there was a lack of objective data and commonly accepted instrument for evaluation. Good practices and further research opportunities are identified. This study has implications for researchers and higher education institutions that are interested in research and practice on increasing general competence in digital accessibility and inclusive education.